Pengaruh Kompetensi Kewirausahaan Dan Orientasi Kewirausahaan Terhadap Kinerja Usaha Pada UMKM Di Kecamatan Sungai Rumbai - Fitriana; Mayroza Wiska; Kelik Purwanto (Jurnal Manajemen dan Bisnis Kreatif, 2023)
The development of the economy in Indonesia cannot be separated from the existence of Micro, Small and Medium Enterprises, as the population increases, the need for jobs also increases, every human being has needs to survive, and needs employment to meet his needs in order to earn money. This study aims to analyze the effect of entrepreneurial competence and entrepreneurial orientation on business performance in umkm in sungai rumbai sub-district. The research method used is quantitative research by collecting data through questionnaires distributed to respondents. The independent variables in this study are entrepreneurial competence and entrepreneurial orientation, while the dependent variable is business performance. The results show that the variables of entrepreneurial competence and entrepreneurial orientation simultaneously have a significant positive effect on business performance as evidenced by fcount (77.533) > ftabel (3.101). The entrepreneurial competency variable is indicated by the results of the t value of 5.604 and t table 1.662 where t count is greater than t table (5.604> 1.662) and the level of significance value is less than alpha (0.000 <0.05), it can be obtained Ho is rejected and H1 is accepted. The entrepreneurial orientation variable t value is 4.150 and t table 1.662 where t count is greater than t table (4.150> 1.662) this shows that the independent variable of entrepreneurial orientation has a positive and significant effect on the dependent variable of business performance, and the level of significance is less than alpha (0.000 <0.05) it can be obtained Ho is rejected and H2 accepted.